PERANCANGAN USER INTERFACE (UI) DESIGN UNTUK WEBSITE FREEMIE DENGAN METODE DESIGN THINKING - Praciska, Mia Tri (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
Freemie is a brand from a company engaged in the Food and Beverage (F&B) sector, which focuses on processed noodle products. The design thinking method is used to help design a better and more functional Freemie website interface. This method involves five stages: empathize, define, ideate, prototype and test. Using system evaluation with the useberry testing tool and calculating test results using SEQ (Single Ease Question) and SUS (System Usability Scale). The average value of SEQ was obtained, namely task 1 was 5.8 and task 2 was 6.2 and the results of the SUS calculation were 89.6. This means that the design succeeds in providing a better understanding of user needs and design adjustments that are tailored to user preferences and needs.